Oral fingolimod for chronic inflammatory demyelinating polyradiculoneuropathy (FORCIDP Trial): a double-blind, multicentre, randomised controlled trial. Issue 8 (August 2018) - Hughes, Richard; Dalakas, Marinos C; Merkies, Ingemar; Latov, Norman; Léger, Jean-Marc; Nobile-Orazio, Eduardo; Sobue, Gen; Genge, Angela; Cornblath, David; Merschhemke, Martin; Ervin, Carolyn Marie; Agoropoulou, Catherine; et al.
Summary: Background: Fingolimod is approved for the treatment of relapsing-remitting multiple sclerosis and was effective in experimental autoimmune neuritis in rats, a possible model for chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). We aimed to evaluate the efficacy of fingolimod in delaying disability progression in patients with CIDP who withdrew from currently effective treatments (intravenous immunoglobulin [IVIg] or corticosteroids). Methods: This double-blind, multicentre, randomised, placebo-controlled, parallel-group, event-driven study was done at 48 neurology centres in Australia, Canada, Israel, Japan, the USA, and nine countries in Europe. Participants with CIDP who were receiving IVIg or corticosteroids were randomly assigned (1:1) to once-daily oral fingolimod 0·5 mg or placebo. Owing to the event-driven design, treatment duration was flexible and could be up to 4·5 years. Randomisation was done with an automated interactive voice response-web response system and was stratified by Inflammatory Neuropathy Cause and Treatment (INCAT) disability scale scores. Previous IVIg treatment was discontinued after one final course ending the day before the first dose of fingolimod or placebo was given, whereas corticosteroids were tapered off over 8 weeks after randomisation. The primary endpoint was time to first confirmed worsening (≥1 point increase on the adjusted INCAT disability scale score versus baseline) and was assessed in the full analysis set, which consisted of all patients who underwent randomisation and had at least one efficacy assessment for the primary analysis. The survival distribution functions of time to first worsening were estimated within each treatment group according to the Kaplan-Meier survival distribution function and compared with a stratified log-rank test. The trial is registered withClinicalTrials.gov, numberNCT01625182 . Findings: Of 106 participants randomly assigned between Jan 24, 2013, and March 10, 2016, 54 received fingolimod (41 who had been receiving IVIg and 13 who had been receiving corticosteroids) and 52 received placebo (41 who had been receiving IVIg and 11 who had been receiving corticosteroids). The trial ended for futility as recommended by an independent data monitoring committee after an interim analysis when 44 confirmed worsening events had occurred. At the end of the study, the survival estimate of the proportion of participants free from confirmed worsening was not significantly different between the fingolimod group (42%, 95% CI 23–60) and the placebo group (43%, 28–59; p=0·91). Adverse events occurred in 41 (76%) participants receiving fingolimod and 44 (85%) on placebo, and serious adverse events occurred in nine (17%) and four (8%) patients, respectively. The most common adverse events with fingolimod were headache (12 [22%] patients), hypertension (ten [19%]), and extremity pain (seven [13%]). Adverse events leading to study discontinuation occurred in seven (13%) participants on fingolimod and none on placebo. Interpretation: Fingolimod 0·5 mg once-daily was not better than placebo for the treatment of CIDP. Future trial designs should take account of the possibility that if IVIg is stopped abruptly, some patients might relapse soon afterwards whereas others might remain in remission. Funding: Novartis Pharma.